Do the means affect the ends? Radical tactics influence motivation and action tendencies via the perceived legitimacy and efficacy of those actions. (24th August 2022) - Lizzio‐Wilson, Morgana; Thomas, Emma F.; Louis, Winnifred R.; Amiot, Catherine E.; Bury, Simon M.; Molenberghs, Pascal; Decety, Jean; Crane, Monique F.
Abstract: Identity, injustice and group efficacy are key motivations for collective action engagement. However, little work has examined factors that influence their emergence. Across three studies (total N = 938), we test whether exposure to different actions (i.e., radical or conventional) and the perceived legitimacy and efficacy of those actions ('the means') predict observers' sense of injustice, identity, group efficacy about the issue, and in turn, future action engagement ('the ends'). As expected, radical (versus conventional) actions were perceived as less legitimate and effective. These evaluations indirectly predicted lower action via diminished identification and injustice, respectively. Paradoxically, legitimacy and efficacy evaluations also indirectly predicted higher radical and conventional action via diminished group efficacy. Thus, collective action is shaped by and reciprocally influences injustice, identity, and group efficacy. Simultaneous exposure to conventional and radical actions also offset these effects, indicating that conventional actions can mitigate the indirect effects of radical tactics.